In Vitro Protective Effects of a Standardized Extract From Cynara Cardunculus L. Leaves Against TNF-α-Induced Intestinal Inflammation - Speciale, Antonio; Muscarà, Claudia; Molonia, Maria Sofia; Toscano, Giovanni; Cimino, Francesco; Saija, Antonella (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) represents a group of progressive disorders characterized by recurrent chronic inflammation of the gut. New unconventional therapies based on plant derived compounds capable of preventing and/or reducing acute or chronic inflammation could represent a valid alternative for the treatment or prevention of IBDs. Cynara cardunculus L. leaves, considered a food-waste suitable as a rich source of bioactive polyphenols including luteolin and chlorogenic acid, has been reported for its positive effects in digestive tract. The aim of the present work was to evaluate the in vitro molecular mechanisms of beneficial effects of a standardized polyphenol-rich extract obtained from the leaves of Cynara cardunculus L. (CCLE) against acute intestinal inflammation induced by TNF-α on intestinal epithelial Caco-2 cells. CCLE prevented TNF-α-induced NF‐κB inflammatory pathway and the overexpression of IL-8 and COX-2. In addition, CCLE was able to improve basal intracellular antioxidant power in both TNF-α-unexposed or -exposed Caco-2 cells and this effect was associated to the activation of Nrf2 pathway, a master regulator of redox homeostasis affecting antioxidant and phase II detoxifying genes, stimulating an adaptive cellular response. In conclusion, our data clearly evidenced that, although considered a waste, Cynara cardunculus leaves may be used to obtain extracts rich in bioactive polyphenols potentially useful for prevention and treatment of inflammatory intestinal diseases.